T lymphocytes with a normal ADA gene accumulate after transplantation of transduced autologous umbilical cord blood CD34(+) cells in ADA-deficient SCID neonates - Kohn, Donald B. (1998)
Adenosine deaminase-deficient severe combined immunodeficiency was the first disease investigated for gene therapy because of a postulated production or survival advantage for gene-corrected T lymphocytes, which may overcome inefficient gene transfer. Four years after three newborns with this disease were given infusions of transduced autologous umbilical cord blood CD34(+) cells, the frequency of gene-containing T lymphocytes has risen to 1–10%, whereas the frequencies of other hematopoietic and lymphoid cells containing the gene remain at 0.01–0.1%. Cessation of polyethylene glycol-conjugated adenosine deaminase enzyme replacement in one subject led to a decline in immune function, despite the persistence of gene-containing T lymphocytes. Thus, despite the long-term engraftment of transduced stem cells and selective accumulation of gene-containing T lymphocytes, improved gene transfer and expression will be needed to attain a therapeutic effect.